INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN KREATIF DI RUMAH KREATIF WADAS KELIR PURWOKERTO - Sumiarti Sumiarti (Jurnal Penelitian Agama, 2016)
Abstract: Creative Learning implemented by Rumah Kreatif Wadas Kelir (RKWK) has been integrating the values of character education in the learning process Creative learning undertaken to develop the creative intelligence of the students in terms of the richness of ideas and encourage children to realize the ideas he has in the form of real work, for example: poetry, short stories, fairy tales, songs, dance, and so on. The process of integration of the values of character education implemented in a planned and integrated in the learning process is carried out. So the process of character education is not taught, but immediately put into practice in creative learning activities and internalized through interaction between teachers and learners. Keywords: Learning, Integration, Creative.